Integration of Non-Terrestrial Network for 5G IoT and Future 6G - Wong, Oi Shan; Gregory, Mark A; Li, Shuo (Journal of Telecommunications and the Digital Economy, 2025)
The exponential growth of the Internet of Things (IoT) has spurred the need for robust and extensive connectivity solutions. In response to the market and use-case requirements, the Third Generation Partnership Project (3GPP) introduced Narrowband IoT (NB-IoT). The latest NB-IoT integration with Non-Terrestrial Network (NTN) aims to bridge the coverage gaps in challenging terrains and address capacity issues in dense urban environments through the utilisation of satellites and Unmanned Aerial Vehicles (UAVs). This research paper explores the potential of NTN systems to complement and enhance the capabilities of 5G NB-IoT and 6G technologies. Through a combination of academic research and simulation, it seeks to evaluate the advantages of NTN, such as extended coverage and improved signal quality, for massive IoT device connectivity. Our simulation results demonstrate a trade-off between coverage and network capacity: while higher UAV altitudes provide extensive coverage by reaching more receivers, they also suffer from reduced signal strength and capacity due to increased path loss. This paper provides an overview of technical specifications and challenges related to NB-IoT and NTN, an assessment of NB-IoT NTN performance in a real-world scenario, and an analytical framework with simplified graphical representations for evaluating NTN integration into NB-IoT.